2006
DOI: 10.1111/j.1468-2982.2006.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Abnormalities in Sporadic Hemiplegic Migraine on Conventional MRI, Diffusion and Perfusion MRI and MRS

Abstract: Prolonged hemiparetic migraine aura can cause diagnostic confusion and be mistaken for ischaemic stroke occurring during the course of a migraine--'migrainous infarction'. We report a case of prolonged hemiparesis occurring during the course of a migraine attack. Though initially confused with migrainous infarction, we suggest with sequential magnetic resonance imaging, magnetic resonance angiography, diffusion, perfusion images and magnetic resonance spectroscopy that the hemiplegia was not of vascular origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 17 publications
2
47
0
4
Order By: Relevance
“…The hypothesis of a mitochondrial deficiency was also put forward by a study in which decreased NAA was found in the (left) thalamus of MwoA patients (36). Finally, a reduced NAA concentration was also found at rest in the cerebellum of FHM1 patients (37), in the left temporoparietal cortex (site of migrainous stroke) of a sporadic hemiplegic migraine (SHM) patient (38) and in the occipital cortex of another SHM patient (39), which has been rather attributed to neuronal impairment or loss. The latter is obvious in migrainous stroke but may also fit with the frequently observed cerebellar atrophy in FHM (40).…”
Section: Naamentioning
confidence: 93%
See 2 more Smart Citations
“…The hypothesis of a mitochondrial deficiency was also put forward by a study in which decreased NAA was found in the (left) thalamus of MwoA patients (36). Finally, a reduced NAA concentration was also found at rest in the cerebellum of FHM1 patients (37), in the left temporoparietal cortex (site of migrainous stroke) of a sporadic hemiplegic migraine (SHM) patient (38) and in the occipital cortex of another SHM patient (39), which has been rather attributed to neuronal impairment or loss. The latter is obvious in migrainous stroke but may also fit with the frequently observed cerebellar atrophy in FHM (40).…”
Section: Naamentioning
confidence: 93%
“…It is possible that the signal-to-noise ratio, in particular in 31 (11,12). In a few studies information concerning coil specification was lacking (37)(38)(39)49). Table 4 describes which MRS localization technique was used in each study.…”
Section: Magnetic Field Strength and Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,11 DSC and nuclear medicine studies have shown postaura hyperperfusion in the cortex affected by the hemiplegic migraine. 3,11,[36][37][38] As opposed to ASL, nuclear medicine studies and contrast bolus techniques are not easily repeatable, require radiopharmaceuticals that must be prepared in advance, and can require multi-day examinations to avoid double dosing.…”
Section: 28mentioning
confidence: 99%
“…Spectroscopy study showed reduced NAA/Cr. To explain these results, in the absence of vascular occlusion, the authors suggested a metabolic alteration at cellular level with a spreading cortical depression leading to damage of the ATPase pump with altered membrane permeability [45].…”
Section: Migraine With Auramentioning
confidence: 99%